Customer satisfaction at foreign trade department of Bank Asia Limited, Mohakjhali branch. - Tanny, Anisha (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.